Audit committee attributes and corporate fraud / Maliah Alwi - Alwi, Maliah (2013)
The objective of this study is to examine the relationship between audit committee attributes (audit committee independent, expertise, meeting, gender and ethnicity) and the propensity of fraudulent financial reporting. The sample includes 116 frauds and non-fraud companies listed on Bursa Malaysia from the year 2005 to 2010. The finding of this study indicates that the audit committee's independence is positively associated with fraudulent financial reporting. The higher proportion of independent or outside director in the committee, the higher the propensity of financial fraud occurrences. The results also show that, the audit committee expertise is negatively associated with the corporate fraud. This suggests that when audit committee members are financially literate, they are more competent to curb fraudulent financial reporting. However, the finding for audit committee meeting, gender and ethnicity show that there is no relationship between these variables with the corporate fraud. The result of this study is robust after controlling the other firm-specific effects.